Assessing the development of primary English education based on CIPP model—a case study from primary schools in China - Chang, Xiao; Wang, Zhe (Frontiers in Psychology, 2024)
This article examines the development of primary English education from teachers’and students’ perspectives; this is done by investigating environment, curriculum and teacher and students’ information. The study was carried out with 42 primary English teachers and 404 primary students from 90 urban and rural primary schools in 13 regions in the Hunan Province, China, the participants engaged in the questionnaire tasks to investigate the present status and problems with primary English education in the Hunan Province. Based on the assessment indicators through CIPP model, combining educational theory and sustainable development theory, the present study develops a primary school English education evaluation model and conducts a practical investigation of primary school English education in Hunan Province, based on the established model. The findings indicate that the quality of teachers has improved, teaching methods and teaching equipment have become diversified, and student interests and English proficiencies have increased. However, there are still deficiencies in the implementation of Primary English Education in Hunan Province. For instance, certain schools improperly implement national policies, resulting in imbalanced education. Additionally, educational inequality persists due to disparities in family economic status and importance. Moreover, regional, ideological, and management factors contribute to uneven allocation of educational resources. Furthermore, significant disparities exist between urban and rural areas in terms of teacher qualifications, teaching quality, and school operating hours. The article proposes enhancing awareness of sustainable development, strengthening supervision, and seeking educational and policy support to facilitate the sustainable development of primary English education.